Yasukuni Shrine history, memory, and Japan's unending postwar - Takenaka, Akiko 1965- (Studies of the Weatherhead East Asian Institute, Columbia University, 2015)
The first extensive English-language study of Yasukuni Shrine as a war memorial. It explores the controversial shrine's role in waging war, promoting peace, honouring the dead, and, in particular, building Japan's modern national identity. It traces Yasukuni's history from its conceptualization in the final years of the Tokugawa period and Japan's wars of imperialism to the present.